A framework proposal for assessing social impacts in subnational circular economy experiments - Juste Rajaonson; Chedrak Chembessi; Pierrick Barcat (Societal Impacts)
As awareness of the sustainability challenges facing global economies grows, many countries are adopting circular economy (CE) policies that prioritize resource reuse, waste reduction, and sustainable production and consumption strategies. Subnational governments are also advancing these efforts by developing CE roadmaps to support the growing momentum of initiatives led by businesses and other stakeholders. However, these policies can lead to unintended social impacts, both positive and negative. In this study, we explore 11 social externality hypotheses identified through a literature review and a case study of Montreal's recent CE roadmap adoption. Preliminary findings suggest that while CE initiatives are known for promoting job creation and strengthening networks, their wider social impacts on well-being, inclusion, finance, culture, education, and justice are often overlooked, with potentially negative consequences underrecognized. This highlights the need for a systematic approach to identify and manage social externalities, helping policymakers enhance the benefits and mitigate the risks associated with CE transitions at the subnational level.